Excretion of infectious hepatitis E virus into milk in cows imposes high risks of zoonosis. Issue 2 (27th June 2016) - Huang, Fen; Li, Yunlong; Yu, Wenhai; Jing, Shenrong; Wang, Jue; Long, Feiyan; He, Zhanlong; Yang, Chenchen; Bi, Yanhong; Cao, Wentao; Liu, Chengbo; Hua, Xiuguo; et al.
Abstract : Hepatitis E virus (HEV) represents the main cause of acute hepatitis worldwide. HEV infection in immunocompromised patients involves a high risk for the development of chronic hepatitis. Because HEV is recognized as a zoonotic pathogen, it is currently believed that swine is the primary reservoir. However, this is not sufficient to justify the strikingly high seroprevalence of HEV in both developing and Western countries. Thus, this study aimed to identify new zoonotic sources that bear a high risk of transmission to humans. We collected fecal, blood, and milk samples of cows in a typical rural region of Yunnan Province in southwest China, where mixed farming of domestic animals is a common practice. HEV RNA was quantified by quantitative real‐time polymerase chain reaction, and the whole genome was sequenced. HEV infectivity was assessed in rhesus macaques. We found a high prevalence of active HEV infection in cows as determined by viral RNA positivity in fecal samples. Surprisingly, we discovered that HEV is excreted into milk that is produced by infected cows. Phylogenetic analysis revealed that all HEV isolates from cow/milk belong to genotype 4 and subtype 4h. Gavage with HEV‐contaminated raw and even pasteurized milk resulted in active infection in rhesus macaques. Importantly, a short period of boiling, but not pasteurization, could completely inactivate HEV. Conclusion : Infectious HEV‐contaminated cow milk is recognized as a new zoonotic source that bears a high risk of transmission to humans; these results call attention to understanding and establishing proper measurement and control of HEV zoonotic transmission, particularly in the setting of mixed farming of domestic animals. (Hepatology 2016;64:350‐359)